2022
DOI: 10.3390/ijms23052562
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Mediated Plant Responses to Nutrient Stress

Abstract: To complete their life cycles, plants require several minerals that are found in soil. Plant growth and development can be affected by nutrient shortages or high nutrient availability. Several adaptations and evolutionary changes have enabled plants to cope with inappropriate growth conditions and low or high nutrient levels. MicroRNAs (miRNAs) have been recognized for transcript cleavage and translational reduction, and can be used for post-transcriptional regulation. Aside from regulating plant growth and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 149 publications
(169 reference statements)
0
23
0
Order By: Relevance
“…Additionally, we noted that some stress-regulated miRNAs, identified in this study, might be fine-tuned across adaptive responses to various stresses. For example, miR169 and miR319 were considered as a bridge, linking plant responses to ABA, drought and salt stress ( De la Rosa et al, 2019 ; Salgado et al, 2021 ); miR398 was reported to play vital roles in various stresses such as water deficit ( Yang et al, 2020 ), oxidative stress ( Li et al, 2020 ), nutrient deficiency ( Islam et al, 2022 ), salt stress ( He et al, 2021 ), and bacterial infection ( Salamon et al, 2021 ). This was probably due to the shared regulatory genes that are modulated by these miRNAs across distinct stress responses, attempting to reveal complex miRNA-mediated gene regulation was involved in the cross-response to abiotic and biotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we noted that some stress-regulated miRNAs, identified in this study, might be fine-tuned across adaptive responses to various stresses. For example, miR169 and miR319 were considered as a bridge, linking plant responses to ABA, drought and salt stress ( De la Rosa et al, 2019 ; Salgado et al, 2021 ); miR398 was reported to play vital roles in various stresses such as water deficit ( Yang et al, 2020 ), oxidative stress ( Li et al, 2020 ), nutrient deficiency ( Islam et al, 2022 ), salt stress ( He et al, 2021 ), and bacterial infection ( Salamon et al, 2021 ). This was probably due to the shared regulatory genes that are modulated by these miRNAs across distinct stress responses, attempting to reveal complex miRNA-mediated gene regulation was involved in the cross-response to abiotic and biotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Biofortification through agricultural biotechnology also relies on the precise genome editing approaches, including the CRISPR-Cas9 and other genome editing strategies and also on the genetic manipulation of regulatory elements, like microRNAs. Besides genome editing, during the recent years, emphasis has been given on the other biotechnological approaches, such as the microRNA mediated regulation of nutrient transporters and metabolic enzymes under the nutrient stress conditions in cereal crops (Islam et al 2022 ). Along with the traditional and marker-assisted plant breeding approaches, biofortification of crops through agricultural biotechnology using less-expensive, rapid and more potential genome editing strategies will provide important tool in the long run to overcome the challenge of global micronutrient malnutrition.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…When confronted with environmental stresses, some miRNAs exhibit altered regulations. Nutrient imbalance [ 27 , 28 ], drought [ 29 , 30 , 31 ], salinity [ 32 , 33 , 34 ], cold [ 35 , 36 , 37 ], heat or high temperatures [ 38 , 39 , 40 ], ultraviolet (UV)-B/C rays [ 41 , 42 ] result in altered expressions of various miRNA families. miR398 was the first miRNA to be directly linked to environmental stress tolerance in plants.…”
Section: Abiotic Stress Responsive Mirnas In Plantsmentioning
confidence: 99%